Coherence - Givón, Talmy, 1936- (John Benjamins Publishing Company, 2020)
"Coherence, connectivity and the fitting together of smaller parts into larger structures are the hallmark of complex biologically-based organized systems. As an internal constraint, coherence allows the parts to work together as a whole. As an external constraint, it lets systems evolve and adapt to novel contexts. As a constraint on information processing, it makes new knowledge accessible to the evolving, maturing, learning mind-brain. As a constraint on cultures, it enables social groups to cooperate. And as a constraint on communication, it allows the language and mind of speakers be accessible to hearers. In this inspiring monograph Givón explores the coherence of biological organisms, the structural and functional coherence of the complex human mind-brain, the evolution of complex social organization and cultures, the coherence of language and communication, as well as relevant offshoots of cognition, socio-culture and communication"--